(untitled) (Canadian Medical Education Journal, 2025)
Background: Over the past three decades, the field of Pediatric Hospital Medicine (PHM) has expanded rapidly in North America in response to the increasing complexity and acuity of the pediatric inpatient population. While 78 fellowship programs and a published PHM Core Competencies framework exist in the United States, Canadian fellowship programs lack a national competency framework to guide curriculum and practice. This absence creates uncertainty in defining the scope of practice and training expectations for PHM in Canada. The purpose of this study was to define this scope. Methods: Using Delphi methodology, a national panel of experts in PHM iteratively rated potential competencies, on a 5-point scale, to determine their priority for inclusion. Responses were analyzed after each round. Competencies that were assigned a rating of three or less by ≥80% of the panelists were removed from subsequent rounds. The remaining competencies were re-sent to panelists for further ratings until consensus was reached, defined as Cronbach’s α ≥0.95 and after a minimum of two survey rounds. At the conclusion of the Delphi process, competencies where ≥80% of the panelists assigned a rating of ≥4 were included. Results: Two rounds of the Delphi process were required to reach consensus. Thirty-five panelists completed both survey rounds. The panelists represented 13 Canadian pediatric tertiary care centers and five community hospitals. Of 176 initial competencies, 109 PHM competencies achieved consensus, spanning the seven CanMEDS roles. Conclusion: This is the first study to define competencies for PHM in Canada. The competencies identified provide a framework for PHM fellowship program directors to shape local curricula. The results may also be used to inform the development of comprehensive national PHM fellowship curricula.